Plasma thrombomodulin levels in early respiratory distress syndrome - Yurdakök, Murat; Yiğit, Şule; Aliefendioğlu, Didem; Dündar, Semra; Kirazlı, Şerafeddin (The Turkish Journal of Pediatrics, 1998)
Infants with respiratory distress syndrome (RDS) undergo hemodynamic alterations in both the pulmonary and systemic vascular beds that predispose these infants to microvascular damage. In addition, disseminated intravascular coagulation (DIC) is frequently encountered in preterm infants with advanced RDS. In preterm infants with RDS, the plasma status is not known. Therefore, we studied plasma thrombomodulin levels in 25 preterm infants who did or did not develop RDS within the first few hours of life. The mean plasma thrombomodulin levels were found to be similar in the two groups ( 8.12 ± 10.20 ng/ml vs. 18.30 ± 22.77 ng/ml, respectively, p > 0.05 by Mann-Whitney U test). It seems that plasma thrombomodulin levels are normal in the earlier stages of RDS before the occurrence of severe vascular damage and DIC due to hypoxemia.
Keywords: newborn infant; thrombomodulin; respiratory distress syndrome